2012
DOI: 10.1107/s1744309112048002
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization and preliminary X-ray analysis of human MTH1 with a homogeneous N-terminus

Abstract: Human MTH1 (hMTH1) is an enzyme that hydrolyses several oxidized purine nucleoside triphosphates to their corresponding nucleoside monophosphates. Crystallographic studies have shown that the accurate mode of interaction between 8-oxoguanine and hMTH1 cannot be understood without determining the positions of the H atoms, as can be observed in neutron and/or ultrahigh-resolution X-ray diffraction studies. The hMTH1 protein prepared in the original expression system from Escherichia coli did not appear to be sui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…We previously reported that hMTH1(G2K) (it has a homogeneous N terminus) shows a new crystal form with high diffraction quality (1.2 Å) at neutral pH. In addition, the catalytic activity of hMTH1(G2K) toward 8-oxo-dGTP is almost identical to that of the wild type ( 32 ). Hereafter, hMTH1(G2K) is referred to as hMTH1 or the wild type for simplicity.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…We previously reported that hMTH1(G2K) (it has a homogeneous N terminus) shows a new crystal form with high diffraction quality (1.2 Å) at neutral pH. In addition, the catalytic activity of hMTH1(G2K) toward 8-oxo-dGTP is almost identical to that of the wild type ( 32 ). Hereafter, hMTH1(G2K) is referred to as hMTH1 or the wild type for simplicity.…”
Section: Resultsmentioning
confidence: 94%
“…D120N or D120A mutations were introduced using the KOD-Plus-Mutagenesis Kit (Toyobo). The pET8c plasmid encoding hMTH1(G2K) served as a template ( 32 ). PCRs were performed with appropriate primers: 5′- AAC AGCTACTGGTTTCCACTCCTGCT-3′ for the D120N mutant and 5′- CAG CTACTGGTTTCCACTCCTGC-3′ for the D120A mutant (the mutation sites are underlined), with 5′-ATCGGGCCACATGTCCTTGAAGGG-3′ as a general reverse complementary primer for both mutants.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was shown that MTH1 inhibitors, such as TH287, TH588 and (S)-crizotinib, were sufficient to produce DNA breaks and induce tumour suppressor responses (13,17). Researchers have expressed recombinant human MTH1 protein in Escherichia coli for crystallisation (18)(19)(20) and inhibition experiments (13,17,21). However, there have been few reports on the optimised expression of hMTH1, as well as its purity and enzymatic activity, which are key factors for inhibitor screening and the functional analysis of hMTH1…”
Section: Introductionmentioning
confidence: 99%